POTENSI EKSTRAK N-HEKSAN, DIKLOROMETANA, ETIL ASETAT, DAN ETANOL 70% JAMUR DEWA (Agaricus blazei Murill) TERHADAP SEL MCF-7 - Misgiati, Misgiati - (Jurnal Riset Kefarmasian Indonesia, 2022)
God mushroom is a functional food. It has pharmacological activity. This content has activity as an anticancer. The purpose of this study was to conduct a preliminary test to obtain an active ingredient capable of having anticancer activity on MCF-7 cells. The stages of the research are stratified extraction with several solvents. Extraction using maceration. The resulting extract was identified and tested for the anticancer activity of MCF-7 cells. The test uses the TLC method. The stationary phase with silica GF254, the mobile phase is n-hexane: ethyl acetate. Anticancer activity test using the MTT method. The results of the identification of each extract contained terpenoid secondary metabolites. Anticancer activity of MCF-7 cells with IC50 extract of n-hexane 15.0923 µg/ml, dichloromethane extract 17.4213 µg/ml, ethyl acetate extract 10.9132µg/ml with strong cytotoxicity criteria, while for ethanol extract IC50 675, 1236 µg/ml.